Phytotoxicity of coal fly ash on plant growth and heavy metal uptake by plant in an acid soil - Nisma Ula Shoumi Rahmawati; Novi Rahmawati Sutopo; Yulia Nuraini; Eko Handayanto (Journal of Degraded and Mining Lands Management, 2020)
Considering the content of various elements in coal fly ash (CFA),  it has the potential to be used as an additional source of nutrients in the soil. However, the use of CFA for agriculture is still debated because CFA contains several metal elements. The purpose of this study was to study the CFA phytotoxicity to seed germination and metal uptake by plants on acid soil. The first experiment was the study of the effect of extracts of various CFA and soil mixtures (5% - 45% CFA) on the germination of mustard seeds. The second study was a CFA phytotoxicity test for plant growth and metal uptake by the mustard plant. Results of the first experiment showed that the application of CFA had no significant effect on mustard seed germination, but had a significant effect on radicle length. CFA application increased the uptake of Pb and Cu by plant along with the increase in the proportion of CFA in the CFA + soil mixture. The contents of Cu and Pb in the mustard plant due to CFA application up to 30% were still below the threshold levels of Cu (36 ppm) and Pb (2 ppm).